2007
DOI: 10.1016/j.nuclphysbps.2007.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Model-dependent radiative corrections to revisited

Abstract: The long-distance electromagnetic radiative corrections to τ − → π − π 0 ντ are re-evaluated. A meson dominance model is used to describe the emission of real photons in this decay. Results obtained for the hadronic spectrum and the decay rate in photon inclusive reactions are compared with previous calculations based on the chiral resonance theory. Independent tests in τ → ππνγ that can help to validate the predictions of one of the two models are briefly discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 21 publications
2
35
1
Order By: Relevance
“…Equivalently, if we exclude only the contributions involving an intermediate a 1 (1260) state (Figures 2.e, 2.f, 2.j and 2.k of ref. [11]), the values obtained for G EM (t) almost overlap the solid line in Figure 1. The simple formula (x ≡ t/m 2 τ ):…”
Section: Long-distance Corrections To the Di-pion Spectrumsupporting
confidence: 69%
See 4 more Smart Citations
“…Equivalently, if we exclude only the contributions involving an intermediate a 1 (1260) state (Figures 2.e, 2.f, 2.j and 2.k of ref. [11]), the values obtained for G EM (t) almost overlap the solid line in Figure 1. The simple formula (x ≡ t/m 2 τ ):…”
Section: Long-distance Corrections To the Di-pion Spectrumsupporting
confidence: 69%
“…Given all these considerations, in ref. [11] we have used a meson dominance model to study the effects of model-dependent contributions in different observables associated with radiative τ 2π decays. We have found that some of these observables exhibit important differences with respect to the results of ref.…”
Section: Long-distance Corrections To the Di-pion Spectrummentioning
confidence: 99%
See 3 more Smart Citations